Thyrotoxic crisis presenting with jaundice - Wickramasinghe, R. D. S. S. (BMC Res Notes, 2016)
BACKGROUND: Thyrotoxic crisis is a medical emergency requiring early diagnosis and urgent management, which can be challenging due to its diverse clinical presentations. While common presentations include fever, sweating, palpitations, tremors and confusion, presence of jaundice is rare. CASE PRESENTATION: We report a 35-year-old male who presented with jaundice due to cholestasis along with other features of thyrotoxic crisis due to Graves’ disease. He had a good clinical recovery with resolution of cholestasis following treatment for thyrotoxic crisis. CONCLUSION: Jaundice can be a rare manifestation of thyrotoxic crisis, and should be considered in the differential diagnosis when other clinical features of thyrotoxic crisis are present. However secondary causes of jaundice should be looked into and excluded. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13104-016-2126-z) contains supplementary material, which is available to authorized users.